Analysis and forecast spatiotemporal distribution of thunderstorms and hail the territory of Belarus - Lopukh, Piotr S.; Berazhkova, Katsiaryna S. (Journal of the Belarusian State University. Geography and Geology, 2019)
The article is devoted to the study of the problem of ensuring the safety of aircraft during take-off and landing. Thunderstorm and hail is one of the most dangerous meteorological phenomena in aviation. To prevent accidents associated with these phenomena, it is necessary to clearly understand the patterns of their occurrence and spatial distribution. In connection with the rapid growth of passenger and cargo traffic, it is necessary to be able to receive and provide actual meteorological information in real mode, as well as to be able to receive high-quality and timely weather forecast. To study the spatial-temporal patterns of the distribution of thunderstorms and hail, Belgidromet’s meteorological instrumental data for 1989–2016 was processed, synoptic maps were analyzed in comparison with calculated forecasts, including WRF, and maps were made using ArcGIS.